Perancangan Sistem Informasi Pendaftaran Rawat Jalan Berbasis Web di RSUD X - Nursuci Safitri; Yosefina Palimirma Andrianto; Indri Martina Br Ginting S; Siska Saputri (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to design and implement a web-based outpatient registration information system at Regional General Hospital (RSUD) X to overcome issues arising from the manual registration system. The current manual registration system at RSUD X causes problems such as long queues, potential data entry errors, lost files, and difficulty in finding patient medical history. As a result, patient waiting times are longer, the administrative staff's workload increases, and the overall effectiveness of services decreases. The research method used is a qualitative one, which describes various processes in the system, from patient data input to the digital registration receipt output. The system design approach uses the waterfall method. Data collection was carried out through purposive sampling, while data gathering was done through interviews with registration officers, direct observation, and a documentation study in the medical records unit. The system is built with a combination of technologies, including PHP as a server-side programming language and MySQL as the database. The result is a web-based outpatient registration information system that can improve the efficiency and quality of hospital services. The advantages of this system include wide accessibility, time efficiency, and effective data management. This system is expected to reduce patient queues, improve the efficiency of the registration process, and simplify patient data management. However, the implementation of this system may face challenges such as limited resources and user skills. Solutions to overcome these challenges are effective resource allocation and user training. Overall, the web-based outpatient registration information system can be an effective solution to improve service quality at RSUD X.